Atypical clinical and laboratory features of fish-tank granuloma: A case report. (October 2018) - Sander, Michael; Isaac-Renton, Judith L; Sander, Megan A
We report a case of cutaneous Mycobacterium marinum infection with the unusual reported features of pruritus and paresthesia. In addition, we report a lack of in-vivo response to antibiotics based on in-vitro susceptibility testing.